THE USAGE OF SOME FIRE RETARDANT CHEMICALS AND ALKYL KETENE DIMER (AKD) IN PAPER PULP - Başboğa, Hülya Varlıbaş; Karademir, Arif (Kahramanmaras Sutcu Imam University, 2022)
This study has been carried out with the purpose of packaging products, used to carry important items, prepared from paper-cardboard packaging papers to be resistant to fire, to prevent the progression of the flame in case of possible combustion, and to protect the material such as valuable documents and goods in the package by preventing the leakage of water into the package during extinguishing. In this study, paper production was carried out from fluting pulp. In this study, paper production was carried out by adding fire-retardant chemicals (BA, BX and AH) or water repellent chemicals (Resin and AKD) into pulp separately and their effects on the technological properties of the papers were examined. It was determined that the fire retardant chemicals added to the pulp could not adhere to the papers and were filtered away. The increase in the amount of fire retardant did not affect the fire resistance properties of the produced papers. In addition to the fact that less burning occurred in all fire retardant paper groups compared to the control sample, the expected result could not be obtained, and a close burning to the control group was observed in the papers. The fire retardant solutions prepared for the pulp were applied to the filter papers and it was determined that the fire retardants adhered to the filter papers and there was a noticeable improvement in the fire resistance properties of the filter papers. Among the fire retardant chemicals applied to the filter papers, the best results were observed in the filter papers in which BX was used. AH did not dissolve in distilled water and clings to the filter papers, causing the highest weight change. The Cobb values of the papers have improved with the usage of both water-repellent chemicals. The highest improvement in Cobb values was obtained with the lowest rate of AKD usage. As a result, it has been determined that water-repellent and fire-retardant chemicals work successfully on paper surfaces, but the application method of fire-retardant chemicals is not the proper way.

Bu çalışmada, önemli eşya taşımak için kullanılan kâğıt-karton ambalaj kâğıtlarından üretilen paketleme ürünlerinin yanmaya karşı dirençli olmasını, olası yanma durumunda ise alevin ilerlemesini önlemek ve söndürme sırasında suyun ambalaj içerisine sızmasını engelleyerek ambalaj içerisindeki kıymetli evrak, eşya gibi malzemeyi en ekonomik ve sürdürülebilir bir şekilde koruma amacıyla çalışmalar yapılmıştır. Bu araştırmada, fluting kağıt hamurundan kağıt üretimi gerçekleştirilmiştir. Çalışma kapsamında yanma geciktirici (BA, BX ve AH) veya su itici kimyasal maddeler (Reçine ve AKD) ayrı ayrı kâğıt hamuru içerisine katılarak kâğıt üretimi gerçekleştirilmiş ve kâğıtların teknolojik özelliklerine etkileri incelenmiştir. Kâğıt hamuruna katılan yanma geciktirici kimyasalların kâğıtlara tutunamadığı ve süzülerek uzaklaştığı belirlenmiştir. Kâğıt hamuru için hazırlanan yanma geciktirici çözeltileri filtre kâğıtlarına uygulanmış ve filtre kâğıtlarında yanma geciktiricilerin tutunarak filtre kâğıtlarının yanma direnci değerlerinde gözle görülür iyileşmenin olduğu belirlenmiştir. Filtre kağıtlarına uygulanan yanma geciktirici kimyasallar arasında en iyi sonuçlar BX in kullanıldığı filtre kağıtlarında gözlemlenmiştir. AH suda çözünmemiş ve filtre kağıtlarında tutunarak en yüksek oranda ağırlık değişimine sebep olmuştur. Her iki su itici kimyasalın kullanımı ile üretilen kağıtların Cobb değerleri iyileşmiştir. Cobb değerlerinde en yüksek iyileşme AKD’nin en düşük oranda kullanılmasıyla elde edilmiştir. Sonuç olarak su itici ve yanma geciktirici kimyasalların kağıt yüzeylerinde başarılı bir şekilde çalıştığı, fakat yanma geciktirici kimyasalların uygulama yönteminin uygun olmadığı belirlenmiştir.
BAZI YANMA GECİKTİRİCİ VE SU İTİCİ KİMYASALLARIN KAĞIT HAMURUNDA KULLANILMASI
Keywords: Timber; Pulp and Paper; Kereste; Hamur ve Kağıt